Challenges and Opportunities for Teachers in Implementing Meaningful Learning at SMP Negeri 2 Beduai - Klarita, Endy Liani; Yuliaty, Farida (LPPM Institut Pendidikan Nusantara Global, 2025)
Meaningful learning​ emphasize experience full learning​ awareness, relevance, and enjoyment so that student can No only remember but also understand and absorb material with good. Research This aim For find challenges and opportunities faced by teachers today apply in -depth learning at SMP Negeri 2 Beduai. The research method used is qualitative descriptive with collect data through studies case studies, surveys, and interviews. Research results show that teachers face a number of challenge like challenge infrastructure, motivation students, roles technology, and also teacher readiness. However, there are also several opportunity For increase implementation learning meaningful, such as collaboration between teachers, utilization technology, as well as existence support government For support implementation learning meaningful this . So it is necessary effort together For overcome challenges and maximize opportunity in apply learning meaningful in school. Research This provide suggestions for help implementation meaningful learning​ for educators and providers​ adequate facilities. This model own significant ability​ For increase quality of education in Indonesia in prepare competitive generation​.